Comparison of intensive versus conventional insulin therapy in traumatic brain injury: a meta-analysis of randomized controlled trials. (12th May 2018) - Núñez-Patiño, Rafael A.; Zorrilla-Vaca, Andres; Rivera-Lara, Lucia
ABSTRACT: Objective : To compare intensive insulin therapy (IIT) and conventional insulin therapy (CIT) on clinical outcomes of patients with traumatic brain injury (TBI). Methods : MEDLINE, EMBASE, Google Scholar, ISI Web of Science, and Cochrane Library were systematically searched for randomized controlled trials (RCTs) comparing IIT to CIT in patients with TBI. Study-level characteristics, intensive care unit (ICU) events, and long-term functional outcomes were extracted from the articles. Meta-analysis was performed with random-effect models. Results : Seven RCTs comprising 1070 patients were included. Although IIT was associated with better neurologic outcome (GOS > 3) (RR=0.87, 95% CI=0.78-0.97; P=0.01; I 2 =0%), sensitivity analysis revealed that one study influenced this overall estimate (RR=0.90, 95% CI=0.80–1.01, P=0.07; I 2 =0%). IIT was strongly associated with higher risk of hypoglycaemia (RR=5.79, 95% CI=3.27–10.26, P<0.01; I 2 =38%). IIT and CIT did not differ in terms of early or late mortality (RR=0.96, 95% CI=0.79–1.17, P=0.7; I 2 =0%), infection rate (RR=0.82, 95% CI=0.59–1.14, P=0.23; I 2 =68%), or ICU length of stay (SMD= –0.14, 95% CI=–0.35 to 0.07, P=0.18; I 2 =45%0.) Conclusions : IIT did not improve long-term neurologic outcome, mortality, or infection rate and was associated with increased risk of hypoglycaemia. Additional well-designed RCTs with defined TBI subgroups should be performed to generate more powerful conclusions.